2003
DOI: 10.1209/epl/i2003-00355-6
|View full text |Cite
|
Sign up to set email alerts
|

Parity-dependent Kondo effect in ultrasmall metallic grains

Abstract: Magnetic properties of nanostructures. PACS. 73.63.-b -Electronic transport in mesoscopic or nanoscale materials and structures.Abstract. -In this Letter we study the Kondo effect in an ultrasmall metallic grain, i.e. small enough to have a discrete energy-level spectrum, by calculating the susceptibility χ of the magnetic impurity. Our quantum Monte Carlo simulations, and analytic solution of a simple model, show that the behavior changes dramatically depending on whether the number of electrons in the grain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For a single magnetic impurity, i.e., for the ''Kondobox'' problem [6], there is already a competition, namely, between Á and T K [7][8][9][10][11][12][13]: If the level spacing Á becomes comparable to the bulk T K , logarithmic Kondo correlations are cut, and the extension of the Kondo screening cloud is actually given by the system size. There is eventually only a single conduction-electron state within the Kondo scale T K around the Fermi energy which is available to form the ''Kondo'' singlet.…”
mentioning
confidence: 99%
“…For a single magnetic impurity, i.e., for the ''Kondobox'' problem [6], there is already a competition, namely, between Á and T K [7][8][9][10][11][12][13]: If the level spacing Á becomes comparable to the bulk T K , logarithmic Kondo correlations are cut, and the extension of the Kondo screening cloud is actually given by the system size. There is eventually only a single conduction-electron state within the Kondo scale T K around the Fermi energy which is available to form the ''Kondo'' singlet.…”
mentioning
confidence: 99%
“…The clean system (circles) shows parity effects as expected. 9 In the odd case, the impurity spin is fully screened at T = 0, while in the even case it remains unscreened or partially screened for all temperatures. In the chaotic system the average T χ 0 only slightly differs from the clean case, since the screening of the impurity spin is closely related to the number N C of dot electrons.…”
Section: B Magnetic Susceptibilitymentioning
confidence: 99%
“…It has been shown that physical quantities strongly deviate from the metallic behavior for ∆ T K , i.e., when the size of the Kondo cloud screening the impurity would become larger than the size of the system. [6][7][8][9][10] For example, they show parity effects, i.e., characteristic differences for an even and odd number of electrons in the system. [11][12][13] Kondo physics in the presence of a chaotic dot geometry and disorder, respectively, has been studied within the Kondo disorder model (KDM) [14][15][16] using Anderson's poor man's scaling approach 17 to calculate the Kondo temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Another is the proximity of some boundary in the host material ( Újsághy et al 2001), for instance in the case of a narrow point contact (Zaránd & Udvardi 1996) or for thin film (Crépieux & Lacroix 2000). Finally the class of systems where a Kondo impurity is placed within a fully coherent, finite size electron sea, as has been realized for instance in the context of "quantum corrals" (Fiete et al 2001), has been also considered (Thimm et al 1999, Affleck & Simon 2001, Cornaglia & Balseiro 2002a, Cornaglia & Balseiro 2002b, Simon & Affleck 2002, Franzese et al 2003, Cornaglia & Balseiro 2003, Lewenkopf & Weidenmuller 2005, Kaul et al 2006, Simon et al 2006.…”
Section: Mesoscopic Fluctuationsmentioning
confidence: 99%
“…The existence of a finite mean level spacing of the electron reservoir will, for instance, clearly modify the Kondo physics drastically for low temperature T ≪ ∆ R . This will affect the conductance (Thimm et al 1999, Simon & Affleck 2002, Cornaglia & Balseiro 2003 as well as thermodynamic properties (Cornaglia & Balseiro 2002a, Franzese et al 2003, and considerable insight can be gained by considering the properties of the ground states and first few excited states of the system (Kaul et al 2006, Kaul et al 2008.…”
Section: Mesoscopic Fluctuationsmentioning
confidence: 99%